Music Technology in Education Channeling and Challenging Perspectives - Eiksund, Øyvind Johan; Angelo, Elin; Knigge, Jens (MusPed:Research, 2020)
This anthology presents research projects that examine the intersection between music, technology and education from a variety of perspectives. The contributors are from a range of educational programs within traditional pre-, primary and lower secondary school education, as well as music performance and technology educational programs. Data for the studies stems from primary and lower secondary school, as well as informal learning environments, in addition to the contributors' respective education programs. The research projects examine a wide range of topics such as gamification of ukulele and song teaching, composition with iPads in the classroom, live looping as an approach to ensemble conducting, authentic music technology learning spaces, music-making in the "laptop-era", sound, the notion of net-based presence, and challenges in higher electronic music education. As this anthology is the first publication in the MusPed:Research series, it also contains an introductory chapter about the series and the research network Musikkpedagogikk i utdanning (MiU). This anthology makes a distinct contribution to the research field of music technology in education and questions educational practices in the school and higher educational levels, the goals and content of music education, and our understanding of music and music creation in itself.